(untitled) (The Scientific Journal of University of Saba Region, 2026)
This study examines Muhammad Mahmoud Al-Zubairi’s novel The Tragedy of Waq al-Waq as a hybrid text with a composite structure, in which five major literary genres converge within a single narrative framework: prose poetry, short story, vision narrative (manāmah), epic, and novel. The study proceeds from the hypothesis that this generic interplay transcends the boundaries of formal experimentation to become an artistic and semantic necessity dictated by the gravity of the national tribulation and the liberatory intentions underpinning the novelistic discourse. The methodology adopts an integrative approach combining descriptive-analytical procedures with both structural and hermeneutic frameworks, while also taking into account the historical and cultural dimension, in order to uncover the structural and semantic functions of each genre within the text. The study reaches a theoretical conclusion that undermines the notion of "generic purity." It demonstrates that the vision narrative (manāmah) provides the visionary space within which supernatural elements are rendered plausible; that prose poetry intensifies emotional experience; that the embedded tale functions as a symbolic equivalent; that the epic spirit elevates events to the level of collective destiny; and that the novel serves as the comprehensive narrative framework that preserves both structural and semantic unity. The way of the analysis indicates that generic hybridity represented an artistic strategy for liberating consciousness and resisting tyranny, revealing an artistic intentionality on the part of Al-Zubairi, whereby the novel becomes a message-bearing manifesto addressed to the Yemeni people and the Arab and Islamic nations at large.